Pride and prejudice - Austen, Jane, 1775-1817 (Oxford World's Classics, 2019)
Jane Austen's Pride and Prejudice centers on the conflict between marrying for love and marrying for economic reasons. None of Mr. Bennet's five daughters can inherit his estate, so they are pressured into finding security in "good" marriages. Elizabeth Bennet, the main character, struggles with the societal pressures of marriage and resists Mr. Darcy's advances and proposals.